IMPROVING THE ABILITY TO ARRANGE WORDS INTO SENTENCES BASED ON MIDDAY ACTIVITIES BY USING WORD PICTURE CARD MEDIA AT CLASS 1.C SD NEGERI 10 KECAMATAN PINGGIR, KABUPATEN BENGKALIS - Raja Usman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This was classroom action research (CAR) consisting of two cycles. The main focus in this study was arranging words into sentences based on midday activities by using word picture card media. The subjects of this study were students at grade 1.C SD Negeri 10 Pinggir. The purpose of this study was to improve students’ learning outcomes. The average score of students learning outcome in pre-cycle was 31.68. then, it increased to 72.68 in cycle I, and 82.80 in cycle II. The minimum achievement criteria set by the school was 70. 57.14% of students did not achieve the KKM while 42.86% of them achieved the KKM in the pre-cycle. Then, in cycle 1 35.71% of the students did not achieve the KKM and the rest 64.29% achieved the KKM; and in Cycle II, all students or 100% of them achieved the KKM. Related to changes in students’ behavior towards self-discipline, discipline, and cooperation between students as well as knowledge of skills in learning, the students’ self-confidence in cycle 1 started to appear for 60.71, MB for 32.14 and SM for 7.14; for discipline MT was 72.18, MB was 39.2: and SM was 17.88. Meanwhile, for the collaboration, MB was 28.57 and SM was 71.43. Then, in Cycle II, for self confidence MT and SM were equally 50.00%; for the discipline MB was 35.71 and BC was 64.29; and for cooperation B was 14.29 and BC was 85.71. In Cycle I, there was only one error (67.86%), and 2 – 3 mistakes (32.14%). In Cycle II there was only 1 error (89.29%) and 2-3 mistakes (10.71%). It can be concluded that the use of picture media increased the activity and the students’ learning outcome in writing words to sentences at elementary school.